Analysis of diesel engine vehicle emissions using egr with temperature variations - Hakim, Fa’iq Taufiqul; Wijaya, M. Burhan Rubai; Abdurrahman; Roziqin, Ahmad (JMEL : Journal of Mechanical Engineering Learning, 2025)
This study aims to analyze the exhaust emissions of diesel engine vehicles with and without the use of the Exhaust Gas Recirculation (EGR) system at engine temperature variations of 60℃, 70℃, and 80℃. The study was conducted on a 2008 Mitsubishi L300 Diesel vehicle to measure the effect of EGR on NOx emissions and soot emissions (smoke opacity). The research method used was an experiment with a quantitative approach. Data were obtained by measuring exhaust gas temperature as an indication of NOx emissions and using a smoke opacity meter to measure the level of vehicle smoke concentration. The results showed that the use of EGR was able to reduce NOx emissions, but increased soot emissions. The higher the engine temperature, the NOx emissions tended to increase both in vehicles with and without EGR. Conversely, soot emissions decreased along with increasing engine temperature. The conclusion of this study is that the EGR system is effective in reducing NOx emissions but has side effects in the form of increased soot emissions. Therefore, optimization of EGR technology needs to be combined with other strategies to reduce the negative impact on air quality.